2010
DOI: 10.5539/elt.v3n3p47
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Attrition of General and Special English Words after Years of Non-Exposure: The Case of Iranian Teachers

Abstract: This study sought to investigate the rate of attrition in general and special vocabulary in and out of context. Participants of the study were 210 male Persian literature teachers with different years of non-exposure to English (2, 4, 5, 6, 7, 8 &10) after graduating from university. They were selected through purposive sampling from among 1000 Persian literature teachers from three provinces, namely Esfahan, Fars and Yasuj. Their age ranged between 25 and 35. The instrument included one translation task. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Interestingly with such a slight drop, a paired sample t-test reveals a significant difference (df = 42, t = 1.88, p = <.001). The rate of forgetting found here is in line with the work of Bahrick (1984), Weltens (1989), Bierling (1990), Abbasian and Khajavi (2010) and Alharthi (2012) and mirrors memory research that attrition occurs relatively soon after the end of a learning session (Baddeley, 1990). On the other hand, the participants' mean scores on receptive and productive word knowledge increase a little at Time 3 (M = 65.77), (M = 37.74) though the gains are not statistically significant.…”
Section: ) Is There a Relationship Between The Initial Achievement Osupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly with such a slight drop, a paired sample t-test reveals a significant difference (df = 42, t = 1.88, p = <.001). The rate of forgetting found here is in line with the work of Bahrick (1984), Weltens (1989), Bierling (1990), Abbasian and Khajavi (2010) and Alharthi (2012) and mirrors memory research that attrition occurs relatively soon after the end of a learning session (Baddeley, 1990). On the other hand, the participants' mean scores on receptive and productive word knowledge increase a little at Time 3 (M = 65.77), (M = 37.74) though the gains are not statistically significant.…”
Section: ) Is There a Relationship Between The Initial Achievement Osupporting
confidence: 76%
“…Previous empirical studies that have contributed significantly to the literature on FL attrition at the lexical level have been focused on situations where learners of English rarely use words they know after the conclusion of formal instruction (e.g. Abbasian & Khajavi, 2010;Bierling, 1990;Marefat & Rouhshad, 2007). However, equally interesting is attrition in situations where some possibly limited use is made of the FL after formal instruction has ceased.…”
Section: The State Of Foreign Language Attrition Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the speed of attrition, some evidence show that a rapid decline of L2 vocabulary would occur soon after formal instruction (e.g., Abbasian & Khajavi, 2010;Alharthi, 2012;Bierling, 1990;Weltens, 1989). For example, Abbasian and Khajavi (2010) studied 210 Persian teachers' rate of vocabulary attrition in general and special vocabulary and found that the speed of attrition increased gradually as the year of non-exposure to English increased.…”
Section: L2 Vocabulary Attritionmentioning
confidence: 99%
“…In terms of the speed of attrition, some evidence show that a rapid decline of L2 vocabulary would occur soon after formal instruction (e.g., Abbasian & Khajavi, 2010;Alharthi, 2012;Bierling, 1990;Weltens, 1989). For example, Abbasian and Khajavi (2010) studied 210 Persian teachers' rate of vocabulary attrition in general and special vocabulary and found that the speed of attrition increased gradually as the year of non-exposure to English increased. Alharthi (2014) investigated 67 Arabian English graduate teachers and the results showed that soon after the formal instruction, drastic attrition was observed among the teachers' vocabulary knowledge and there was slight gain in the second year.…”
Section: L2 Vocabulary Attritionmentioning
confidence: 99%